Embodying the Qur’an: Tahfidz Practice, Religious Habitus, and Qur’anic Consciousness in Muslim Minority Thailand - Munawar, Karam; Rohtih, Wiwin Ainis; Mufid, Miftara Ainul; Zainuddin, Ahmad; Jeeranan Wongphaopan (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
Studies on Qur’anic tahfidz have largely focused on memorization techniques and pedagogical achievement, while the formation of religious consciousness through memorization practices remains underexplored. This study examines how the sabaq method functions as a process of forming Qur’anic habitus and embodied religious consciousness among Muslim students at At-Taqwa School, Chiang Mai, Thailand. Employing a qualitative approach within the framework of the Living Qur’an, data were collected through participant observation, in-depth interviews, and documentation of tahfidz activities. The findings demonstrate that repetitive memorization practices constitute forms of lived engagement with the Qur’an operating through cognitive, affective, and practical dimensions. Memorized verses are not only retained verbally but also connected to moral reflection, emotional attachment, spiritual discipline, and everyday religious conduct. Drawing on Pierre Bourdieu’s concept of habitus, this study argues that tahfidz practices function as mechanisms of religious habituation through which Qur’anic values become embodied within students’ dispositions, bodily routines, and socio-religious subjectivity. In the context of the Muslim minority in Thailand, tahfidz also serves as a medium for reproducing Islamic identity and sustaining Qur’anic culture. This study contributes to Living Qur’an scholarship by repositioning tahfidz as an embodied religious practice rather than merely a pedagogical activity of textual memorization. [Kajian mengenai tahfidz Al-Qur’an selama ini lebih banyak berfokus pada teknik hafalan dan capaian pedagogis, sementara pembentukan kesadaran religius melalui praktik menghafal masih relatif kurang mendapat perhatian. Penelitian ini menganalisis bagaimana metode sabaq berfungsi sebagai proses pembentukan habitus Qur’ani dan kesadaran religius yang embodied pada santri di At-Taqwa School, Chiang Mai, Thailand. Penelitian ini menggunakan pendekatan kualitatif dalam kerangka Living Qur’an dengan teknik pengumpulan data berupa observasi partisipatif, wawancara mendalam, dan dokumentasi kegiatan tahfidz. Hasil penelitian menunjukkan bahwa praktik repetisi hafalan merupakan bentuk lived engagement with the Qur’an yang berlangsung melalui dimensi kognitif, afektif, dan praksis. Ayat-ayat yang dihafal tidak hanya direproduksi secara verbal, tetapi juga dikaitkan dengan refleksi moral, keterikatan emosional, disiplin spiritual, dan perilaku religius sehari-hari. Dengan menggunakan konsep habitus Pierre Bourdieu, penelitian ini menunjukkan bahwa praktik tahfidz berfungsi sebagai mekanisme habituasi religius yang menginternalisasikan nilai-nilai Qur’ani ke dalam disposisi, ritme tubuh, dan subjektivitas sosial-keagamaan santri. Dalam konteks Muslim minoritas di Thailand, tahfidz juga berfungsi sebagai medium reproduksi identitas Islam dan pelestarian budaya Qur’ani. Penelitian ini berkontribusi pada pengembangan studi Living Qur’an dengan memosisikan tahfidz sebagai praktik religius embodied, bukan sekadar aktivitas pedagogis reproduksi teks.]